23+3y=5y-215

Subtract 5y from both sides of the equation.

23+3y-5y=-215

Subtract 5y from 3y.

23-2y=-215

23-2y=-215

Subtract 23 from both sides of the equation.

-2y=-215-23

To write -23 as a fraction with a common denominator, multiply by 55.

-2y=-215-23⋅55

Write each expression with a common denominator of 15, by multiplying each by an appropriate factor of 1.

Multiply 23 and 55.

-2y=-215-2⋅53⋅5

Multiply 3 by 5.

-2y=-215-2⋅515

-2y=-215-2⋅515

Combine the numerators over the common denominator.

-2y=-2-2⋅515

Simplify the numerator.

Multiply -2 by 5.

-2y=-2-1015

Subtract 10 from -2.

-2y=-1215

-2y=-1215

Cancel the common factor of -12 and 15.

Factor 3 out of -12.

-2y=3(-4)15

Cancel the common factors.

Factor 3 out of 15.

-2y=3⋅-43⋅5

Cancel the common factor.

-2y=3⋅-43⋅5

Rewrite the expression.

-2y=-45

-2y=-45

-2y=-45

Move the negative in front of the fraction.

-2y=-45

-2y=-45

Divide each term in -2y=-45 by -2.

-2y-2=-45⋅(-12)

Cancel the common factor of -2.

Cancel the common factor.

-2y-2=-45⋅(-12)

Divide y by 1.

y=-45⋅(-12)

y=-45⋅(-12)

Simplify -45⋅(-12).

Cancel the common factor of 2.

Move the leading negative in -45 into the numerator.

y=-45⋅(-12)

Move the leading negative in -12 into the numerator.

y=-45⋅-12

Factor 2 out of -4.

y=2(-2)5⋅-12

Cancel the common factor.

y=2⋅-25⋅-12

Rewrite the expression.

y=-25⋅-1

y=-25⋅-1

Combine -25 and -1.

y=-2⋅-15

Multiply -2 by -1.

y=25

y=25

y=25

The result can be shown in multiple forms.

Exact Form:

y=25

Decimal Form:

y=0.4

Solve for y 2/3+3y=5y-2/15